Biomarkers of Type II Synthetic Pyrethroid Pesticides in Freshwater Fish. (23rd April 2014) - Kaviraj, Anilava; Gupta, Abhik
Abstract : Type II synthetic pyrethroids contain an alpha-cyano group which renders them more neurotoxic than their noncyano type I counterparts. A wide array of biomarkers have been employed to delineate the toxic responses of freshwater fish to various type II synthetic pyrethroids. These include hematological, enzymatic, cytological, genetic, omic and other types of biomarkers. This review puts together the applications of different biomarkers in freshwater fish species in response to the toxicity of the major type II pyrethroid pesticides and assesses their present status, while speculating on the possible future directions.